Caseous calcification of the mitral annulus - M. B. Belkind; E. A. Butorova; O. V. Stukalova; S. A. Gaman; S. M. Smirnov (Евразийский Кардиологический Журнал, 2023)
Caseous calcification of the mitral annulus (CCMA) is a rare form of degenerative lesion of the mitral valve fibrous ring. It’s a biochemical transformation of calcification area accompanied with formation of masses of a curdled consistency (caseosis). It is usually located in the area of the posterior mitral valve. In most cases, it is asymptomatic or minimally symptomatic, and is an incidental finding during imaging studies. The causes and pathogenesis of CCMA are unknown, however, there is a connection with disorders of calcium and phosphorus metabolism and there is no connection with an valve infection. There is no specific treatment. In cases where CCMA leads to significant disturbances of cardiac hemodynamics and/or there is a high probability of ebolism, it needs to be treated surgically.Differential diagnosis is carried out with other cardiac mass.